Noninvasive paternal exclusion testing for cystic fibrosis in the first five to eight weeks of gestation. Issue 1 (December 2018) - Zeevi, David; Zahdeh, Fouad; Kling, Yehuda; Rosen, Tzvia; Renbaum, Paul; Ron-El, Raphael; Eldar-Geva, Talia; Holzer, Hananel; Levy-Lahad, Ephrat; Altarescu, Gheona
Abstract Prenatal genetic testing is not generally applicable to the very early stages of pregnancy (prior to week 8 gestation), a time period that is crucial to pregnant couples with high risk for transmission of genetic disease to their fetus. Therefore, we developed a new ultra-sensitive targeted next generation sequencing method for noninvasive haplotype-based paternal allele exclusion testing of the cystic fibrosis-associated gene, CFTR . This new method was compared to a conventional library prep and sequencing analysis method and all test results were validated by amniotic fluid testing at later stages of pregnancy. Out of 7 enrolled couples, who provided at least two blood samples (at least one week apart) for noninvasiveCFTR testing, a result was obtained for 6 fetuses. Using the new hypersensitive method, all six couples (100%) received a correct diagnosis for the paternal allele as opposed to 3/6 (50%) when tested with the conventional strategy. Among 4 couples who provided just one early pregnancy blood draw for analysis, diagnosis was possible in one fetus, but only using the ultra-sensitive method. Thus, we describe a novel noninvasiveCFTR screening method which demonstrates unprecedented fetal allele typing accuracy in the earliest stages of pregnancy.